(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of things (IoT) is a concept that motivates researchers to develop their ideas into an innovative application. RPL stands for Routing protocols for low power and lossy networks. RPL is the routing protocol, designed for constrained devices. IPv6 and Low power and Lossy network (LLN) techniques make this protocol more flexible with IoT. It is used to route the packets from the one node to another node. Various issues are observed during the routing. In RPL, Node failure, Mobility, energy consumption and congestion are few problems that are observed during the routing. The above problems lead to some issues like Packet loss, path loss, low packet delivery ratio, High energy consumption, and so on. Existing objective functions OF0 and OF1 are used in the RPL protocols to support static nodes in Destination-Oriented Directed Acyclic Graph (DODAG). In this paper, a solution is introduced to overcome node failure in RPL. The node failure in RPL is addressed by using the energy-aware routing approach in the network. The proposed technique has two mechanisms: finding the node with minimum lifetime and parent selection process. This proposed work is evaluated using COOJA simulator.